A Study Factor of Teacher’s Knowledge for Learning Mathematics Management in Mathematical Proof - Lapyingyong, Narubet; Phiphitthakun, Yupin; Heingraj, Channarong (Ratchaphruek Journal, 2014)
The research aimed to study a necessary factor of teacher’s knowledge for management of teaching and learning mathematical proof of university mathematics instructors by using the research and development. The research was divided into three stages which were stage1) the study of factors concerning mathematical proof learning management by synthesizing theories and related research, stage 2) the development factors of teacher’s knowledge for teaching and learning mathematical proof by using means of a focus group which consisted of 3 groups of participates: (1) mathematics instructor, (2) mathematics educators, and (3) students who had enrolled the mathematical proof. These participants were selected by using the special criteria and voluntarily participated and stage 3)the confirmation of 3 developed factors obtained from the stage 2, namely, mathematical content knowledge, pedagogical knowledge, and knowledge of learners cognition in mathematics. These factors were used to construct a rating-scale questionnaire with 56 items and were administered to 260 mathematics instructors who taught the mathematical proof. The data were analyzed by using the confirmatory factor analysis. The majorfindings of the research revealed that 3 main factors for mathematical proof instruction were pedagogical knowledge, which consisted of curricular knowledge, instructional knowledge, and measurement and evaluation knowledge. Mathematical content knowledge consisted of common content knowledge, specialized content knowledge, and knowledge at the mathematical horizon. Also, knowledge of learners’cognition in mathematics consisted of representations concept of mathematical proof, and constructing and understanding of mathematical concepts.